Vermiculitas quimicamente modificadas com grupos orgânicos contendo cloro e nitrogênio como adsorventes para cátions de cobre (II) em solução aquosa - Santos, Saloana Santina Gomes (2012)
A group of interesting materials for the production of multifunctional solids are the natural phyllosilicates which can be modified through reactions in their interlayer region or surface, resulting in hybrid materials with improved properties. In this work, vermiculite (V), a natural phyllosilicate, was used as support after acid lixiviation in HNO3 in the concentrations of 0.3; 0.5 and 0.8 mol dm-3 for the synthesis of inorganic-organic hybrids by silylation reaction with the silylant agent 3-chloropropyltrimethoxysilane (Cl), reacting subsequently with imidazole molecule (Im). The solids were characterized by X-ray diffractometry, infrared spectroscopy, C, H, N and Cl elemental analysis, nitrogen adsorption/dessorption measurements, thermogravimetry, 29Si and 27Al solid state NMR and scanning electronic microscopy. For reaction in the lixiviated solids, the maximum quantity of anchored silane was 1.57, 2.42 and 2.30 mmol/g for V0,3-Cl, V0,5-Cl and V0,8-Cl, respectively. The solid V0,8-Cl-Im showed the highest number of anchored molecules of imidazole group resulting in 1.38 mmol/g of nitrogen. The modified solids were applied for the copper adsorption from aqueous solution, where the maximum retentions were 2.28, 1.99 and 2.38 mmol/g for V0,3-Cl-Im, V0,5-Cl-Im and V0,8-Cl-Im, respectively. The adsorptive processes were described by pseudo second order kinetic and the equilibrium data fitted to the Langmuir model.